An alternative approach for the chemical control of Fusarium wilt of tomato - A.K. SINHA, N.C. MANDAL and (Indian Phytopathology, 2012)
Effectiveness of 19 non-conventional, mostly non-toxic chemicals in wet seed treatment, used at dilute concentrations (10.4 to 10-2M) in controlling Fusarium wilt of tomato has been tested in potted tomato plants (cv. Patharkuchi) inoculated with Fusarium oxysporum f. sp. lycopersici at the age of 3 weeks. While most of these compounds could reduce wilt symptoms appreciably, cupric chloride, ferric chloride, zinc chloride, manganese sulphate, mercuric sulphate, L-cysteine, IAA and DL-methionine showed very strong protective effect. These reduced leaf symptoms by 52 to 71 %, prevented mortality completely and also limited vascular colonization by the pathogen. Most of the test compounds showed little or no in-vitro fungitoxicity at their effective concentrations and stronger protection was often achieved at lower than higher concentration. It has been concluded, therefore, that these non-conventional chemicals act in plant disease control not so much by any direct toxic action but by inducing resistance in susceptible tomato plants, mediated through host tissue conditioning.